NEW EATING HABITS OF NU STUDENTS - Agzamov, Mark (Nazarbayev University School of Sciences and Humanities, 2025)
The capstone project studies new eating habits and the transition process regarding the food consumption of NU students' lives, who moved from NIS and BIL dormitory life with five times free, healthy meals into NU dormitory life where all responsibility and accountability are on student's own shoulders. The project focuses on the experience of adapting to new conditions and exploring what are the new eating habits of NU dormitory residents, who previously lived in NIS and BIL dormitory, which provided them with five free healthy meals a day. This capstone project uses qualitative research methods, namely, semi-structured interviews as the primary research method. Semi-structured interviews allowed us to explore students’ past and new eating habits, personal experience of transition and challenges with food management. Students struggled with meal planning, often feeling overwhelmed by the need to make everyday decisions and actions that they did not have to do before to acquire food. Despite all the hardships and stress at the beginning students demonstrated their adaptiveness to big changes. Nevertheless, students suffering with independent food preparation at the beginning is proven to be real and something should be done to fix it.
Keywords: Transition; Freshmen Nutrition; University Meal Preparation; Student Eating Habits; University Food Environment; type of access: open access